New C-2-symmetric chiral ketones for catalytic asymmetric epoxidation of unfunctionalized olefins - Song, CE; Kim, YH; Lee, KC; Lee, S; Jin, BW (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Using new C-2-symmetric chiral ketones 4 and 6 as precursors for chiral dioxiranes generated in situ, the asymmetric epoxidation of olefins has been achieved in moderate ee. (C) 1997 Elsevier Science Ltd.
Keywords: GENERATED IN-SITU; DIOXIRANE; ALKENES; OXAZIRIDINES; OXIDATIONS; REACTIVITY; CHEMISTRY